Examining the practice of urban governance using UN-Habitat urban governance index in Gondar city, North West Ethiopia - Ergo Beyene; Acamyeleh Gashu Adam; Amare Sewnet Minale (Cogent Social Sciences, 2023)
One of the outlining challenges of the twenty-first century is managing rapidly urbanizing cities. If managed well and guided by sound urban governance principles, cities can act as instruments of growth, and the goal of urban sustainability can be realized. On the other hand, poorly governed cities can become hubs of poverty, disparity, and conflict. Thus, this study is aimed to explore the implementation of urban governance principles in Gondar city. UN-Habitat’s Urban Governance Index (UGI) is employed as an analytical framework. UGI is a straightforward, easy, and flexible framework suited to measure the quality of urban governance practices in the local context. This study’s data included quantitative and qualitative data related to customer satisfaction in service delivery, citizen charter, access to electricity, waste management, water supply connections, pro-poor water policy, citizen involvement in decision-making, and incentives for the informal market. The result indicated that the highest values had been achieved in the effectiveness and accountability sub-indexes, with scores ranging between 0.65 and 0.56, respectively. Similarly, the lowest values have been recorded in equity and participation sub-indexes with scores between 0.44 and 0.37, respectively. The results revealed that the city still needs to implement sound governance principles. Therefore, attention should be given to implementing good urban governance principles to achieve the city we need that fits the smart city paradigm. Innovative structures with systems to implement UGI should be needed for sustainable urban development and to make our cities livable and competitive in the paradigm of sustainable cities.